Optimization Of Paddy Farming System In Shallow Swamp Land Case Study Of River two Village - Nearti, Yuwinti; Jayanti, Nirmala; Mulyana, Eka (Sriwijaya Journal of Environment, 2025)
The conventional farming system used by farmers is planting paddy fields. Conditions for developing and optimizing the paddy field farming system on shallow swampy land with rainfed soil require various interrelated aspects. The objectives of the study include: 1) providing information on the characteristics, potential, and opportunities of shallow swampy land for agricultural development, analyzing the amount of income for farmers so that they can increase maximum profits for these farmers, 2) optimizing the paddy field farming system based on land, labor and capital in implementing land and water management technology. Determination of respondents intentionally (purposive), the sample taken in this study were 100 rice and purple eggplant farmers. The analysis used income, feasibility and optimization using linear programming. The results showed that the average value of rice farming income was Rp3,641,966.5/Ha and the average value of purple eggplant was Rp3,865,939 in River twoVillage. Farming with the optimization of the farming system is feasible to be cultivated with R/C values of 1.32 and 5.87. Optimization of the shallow swampy rice farming system per hectare is recommended only for purple eggplant farming activities so that the income obtained is more profitable while for labor, the remaining and unused labor is 119 and for unused capital of Rp10,979,640, the optimum income of farmers is Rp3,865,939/Ha/MT.